2014
DOI: 10.1007/s11089-014-0628-y
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing the Body’s Response to Trauma: Resistance, Ritual, and Nervous System Activation

Abstract: This essay describes the body's states of nervous system activation after traumafocusing on intimate partner violence and sexual assault against women-as signs of resistance and posits that caregivers should attend to these phenomena as the body's way of communicating. Trauma triggers nervous system responses. and understanding these responses helps caregivers to read the body language of survivors and thus avoid retraumatizing them in pastoral care. Fundamentally, rather than being seen as symptomatic of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Our analysis found that while the reviewed research describes and analyzes women’s physical and emotional experiences of and reactions to violence, these articles generally do not explain or explicitly conceptualize the body and/or embodied processes. Only six articles provided implicit or explicit definitions of these terms (Helsel, 2015; Mills, 2016; Pain, 2014b; Price, 1999; Pyscher, 2017; Rajah, 2007). This finding is somewhat surprising.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis found that while the reviewed research describes and analyzes women’s physical and emotional experiences of and reactions to violence, these articles generally do not explain or explicitly conceptualize the body and/or embodied processes. Only six articles provided implicit or explicit definitions of these terms (Helsel, 2015; Mills, 2016; Pain, 2014b; Price, 1999; Pyscher, 2017; Rajah, 2007). This finding is somewhat surprising.…”
Section: Resultsmentioning
confidence: 99%
“…One woman living in a shelter describes being “paralyzed with fear” when she first arrived there, still expecting that she might experience violence at any moment (Hydén, 2005, p. 173). Helsel (2015) notes that this paralysis may be rooted in the nervous system’s “freeze” response to trauma. Although the victim may appear helpless to an outside observer, this response preserves energy that may be needed later and may have been developed to avoid or buffer against immediate suffering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process may also play out in therapeutic and counseling settings, particularly among practitioners who push clients far beyond their comfort limits. Helsel (2015) notes that therapists who push their clients to confront triggering experiences too early in the treatment process run the risk of retraumatizing them by forcing exposure to “the same feelings of terror and helplessness they felt at the time of trauma without the tools to lessen the intensity of the experience” (p. 692). Instead, Helsel advocates for practitioners to familiarize themselves with the physical aftereffects of trauma and to teach concrete strategies for self-regulation, such as controlled breathing or meditation.…”
Section: Resultsmentioning
confidence: 99%